Induction therapy with ipilimumab and nivolumab followed by consolidative chemoradiation as organ-sparing treatment in urothelial bladder cancer: study protocol of the INDIBLADE trial - Stockem, C.F.; Mellema, J.J.J.; van Rhijn, B.W.G.; Boellaard, T.N.; van Montfoort, M.L.; Balduzzi, S.; Boormans, J.L.; Franckena, M.; Meijer, R.P.; Robbrecht, D.G.J.; Suelmann, B.B.M.; Schaake, E.E.; et al. (Frontiers in Oncology, 2023)
Studies that assessed the efficacy of pre-operative immune checkpoint blockade (ICB) in locally advanced urothelial cancer of the bladder showed encouraging pathological complete response rates, suggesting that a bladder-sparing approach may be a viable option in a subset of patients. Chemoradiation is an alternative for radical cystectomy with similar oncological outcomes, but is still mainly used in selected patients with organ-confined tumors or patients ineligible to undergo radical cystectomy. We propose to sequentially administer ICB and chemoradiation to patients with organconfined and (locally advanced) muscle-invasive bladder cancer. The INDIBLADE trial is an investigator-initiated, single-arm, multicenter phase 2 trial. Fifty patients with cT2-4aN0-2M0 urothelial bladder cancer will be treated with ipilimumab 3mg/kg on day 1, ipilimumab 3mg/kg plus nivolumab 1mg/kg on day 22, and nivolumab 3mg/kg on day 43 followed by chemoradiation. The primary endpoint is the bladder-intact event-free survival (BI-EFS). Events include: local or distant recurrence, salvage cystectomy, death and switch to platinum-based chemotherapy. We will also evaluate the potential of multiparametric magnetic resonance imaging of the bladder to identify non-responders, and we will assess the clearance of circulating tumor DNA as a biomarker for ICB treatment response. This is the first trial in which the efficacy of induction combination ICB followed by chemoradiation is being evaluated to provide bladder-preservation in patients with (locally advanced) urothelial bladder cancer.